Henry Reed: capstone - Reed, Henry, artist (Colorado State University. Libraries, 2026)
The artist's statement: Through my design and video work, communication is at the front of my mind. I believe that telling a story as simply as possible is the most potent path to achieve the level of communication I strive for. In my video work, I exercise restraint in color, dialogue, and composition to create an atmosphere that is plainly confrontational. In my design work, I'm more inclined toward bold color, a sense of humor, and lightness. Although undeniably different, both practices are united by an informed simplicity and an importance of human connection.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design